A novel shock-induced multistage phase transformation and underlying mechanism in textured Nano-Twinned Cu. (October 2021) - Zhu, Yaxin; Wu, Dun; Zhao, Lv; Liang, Shuang; Huang, Minsheng; Li, Zhenhuan
Abstract: Nano-Twinned (NT) Cu under shock loading parallel to twin planes was investigated via nonequilibrium molecular dynamics (NEMD) simulations, with particular attention to the shock response and intrinsic deformation mechanism. During the shock compression process, a novel multi-stage phase transformation (MPT) scenario, i.e., from FCC phase to BCC phase and then to HCP phase, happens due to shock-enhanced twin boundary (TB) sliding. Both increasing the compressive strain caused by shock and decreasing the twin lamellae in the NT Cu can promote the MPT, with which the yield strength retains but the spallation strength increases. The critical shock pressure triggering the MPT depends exponentially on lamellae twin thickness ( T ). These new results have great potentials for improving the impact resistance of metals by tailoring their internal nanostructures. Graphical abstract: